Fiber-reinforced resin composition and molded article

By using polyolefin resin, free polyamide resin or polyester resin, fiber and modified polyolefin resin in the fiber reinforced resin composition, the problem of insufficient thermal deformation temperature and poor tensile creep resistance under high load in the prior art is solved, and high heat deformation resistance and balanced tensile creep resistance are achieved.

CN116406400BActive Publication Date: 2025-03-28MITSUI CHEMICALS INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180078391.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-24
Filing Date
2021-11-24
Publication Date
2025-03-28
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

The conventional fiber reinforced resin compositions have insufficient thermal deformation temperature under high loads, and the thermal deformation temperature is difficult to increase under the condition of adding a compatibilizer, and at the same time, long-term physical properties such as tensile creep resistance are poor.

Method used

A fiber-reinforced resin composition containing a polyolefin resin, a free polyamide resin or a polyester resin, a fiber and a modified polyolefin resin is used to ensure excellent impregnation properties of the resin components, and the heat deformation resistance and tensile creep resistance of the composition are improved by the modified polyolefin resin.

Benefits of technology

It achieves excellent heat deformation resistance under high load, and maintains the balance between heat deformation resistance and tensile creep resistance under the condition of containing a compatibilizer, while improving the interaction between fiber and resin, thereby improving the mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004239936700000251
    Figure GDA0004239936700000251
  • Figure GDA0004239936700000261
    Figure GDA0004239936700000261
  • Figure GDA0004239936700000271
    Figure GDA0004239936700000271
Patent Text Reader

Abstract

A fiber-reinforced resin composition comprising a polyolefin resin (A), one or more resins (B) selected from a polyamide resin (B1) and a polyester resin (B2), a fiber (C), and a modified polyolefin resin (D) at a specific ratio, wherein the melt viscosity η of the polyolefin resin (A) at 250° C. at a shear rate of 120 / sec is A The melt viscosity η of the resin (B) at 250°C at a shear rate of 120 / sec B The ratio η A / η B In the range of 0.3 to 1.3. According to the present invention, a fiber-reinforced resin composition having excellent heat deformation resistance under high load and excellent balance between heat deformation resistance and tensile creep resistance while containing a compatibilizer can be provided. In addition, the fiber-reinforced resin composition of the present invention has excellent impregnation into long fiber glass fibers, thereby improving the interaction between the fibers and the resin composition, which helps to improve mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a fiber-reinforced resin composition and a molded article comprising the same. Background Art

[0002] Fiber-reinforced resins obtained by dispersing various reinforcing fibers in thermoplastic resins have high strength, rigidity, impact resistance, and heat resistance, and have been used for various purposes. Patent Document 1 discloses that the following fiber-reinforced resin composition exhibits a high heat deformation temperature, and the fiber-reinforced resin composition contains polypropylene, polyamide or polyphenylene sulfide, and aminosilane-treated glass fibers in combination at a specific ratio.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-231758 Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the material application of applying a large force for a long time, for the fiber-reinforced resin composition, it is required that the material does not deform even if it is used for a long time. However, in the fiber-reinforced resin composition of patent document 1, the heat deformation temperature under high load is not sufficiently high. In addition, it is recorded in patent document 1 that if a compatibilizer such as modified polypropylene resin is added to the fiber-reinforced resin composition, there is a worry that the heat deformation temperature cannot be improved. However, when a compatibilizer is not added, sometimes long-term physical properties (such as tensile creep resistance) are poor. In addition, by making the resin component used in these reinforced fiber resin compositions excellent in impregnation into the fiber, the interaction between the fiber and the resin component will become stronger, and therefore, the improvement of impregnation is necessary for improving mechanical properties, heat resistance, and durability.

[0008] An object of the present invention is to provide a fiber-reinforced resin composition having excellent heat deformation resistance under high load, excellent balance between heat deformation resistance and tensile creep resistance while containing a compatibilizer, and excellent impregnation property of the contained resin component into reinforcing fibers.

[0009] Means for solving problems

[0010] The inventors of the present application have conducted studies to solve the above problems and have found that the above problems can be solved by using the fiber-reinforced resin composition described below, thereby completing the present invention. The present invention relates to the following [1] to [8].

[0011] [1] A fiber-reinforced resin composition comprising:

[0012] Polyolefin resin (A),

[0013] One or more resins (B) selected from the group consisting of polyamide resins (B1) and polyester resins (B2),

[0014] Fiber (C), and

[0015] Modified polyolefin resin (D);

[0016] In 100 parts by mass of the total content of the polyolefin resin (A), the resin (B) and the fiber (C), the content of the polyolefin resin (A) is 5 to 60 parts by mass, the content of the resin (B) is 5 to 60 parts by mass, and the content of the fiber (C) is 10 to 70 parts by mass,

[0017] The content of the modified polyolefin resin (D) is 0.05 to 0.95 parts by mass relative to 100 parts by mass of the total content of the polyolefin resin (A), the resin (B) and the fiber (C).

[0018] The melt viscosity η of the polyolefin resin (A) at 250°C at a shear rate of 120 / sec A The melt viscosity η of the resin (B) at 250°C at a shear rate of 120 / sec B The ratio η A / η B In the range of 0.3 to 1.3.

[0019] [2] The fiber-reinforced resin composition according to [1], wherein the resin (B) is the polyamide resin (B1).

[0020] [3] The fiber-reinforced resin composition according to [1] or [2], wherein the polyamide resin (B1) is polyamide 6.

[0021] [4] The fiber-reinforced resin composition according to any one of [1] to [3], wherein the content of the resin (B) is 8 to 92 parts by mass based on 100 parts by mass of the total content of the polyolefin resin (A) and the resin (B).

[0022] [5] The fiber-reinforced resin composition according to any one of [1] to [4], wherein the polyolefin resin (A) is polypropylene.

[0023] [6] The fiber-reinforced resin composition according to any one of [1] to [5], wherein the fiber (C) is at least one selected from glass fibers and carbon fibers.

[0024] [7] A molded article comprising the fiber-reinforced resin composition according to any one of [1] to [6].

[0025] [8] The molded article according to [7], which is an automobile part.

[0026] Effects of the Invention

[0027] According to the present invention, a fiber-reinforced resin composition having excellent heat deformation resistance under high load and excellent balance between heat deformation resistance and tensile creep resistance can be provided while containing a compatibilizer. In addition, the fiber-reinforced resin composition of the present invention has excellent impregnation into long fiber glass fibers, thereby improving the interaction between the fiber and the resin composition, which helps to improve mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] Figure 1 This is a schematic diagram of a mold used for evaluation of impregnation properties in Examples. DETAILED DESCRIPTION

[0029] Hereinafter, the present invention will be described in more detail.

[0030] In the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0031] [Fiber-reinforced resin composition]

[0032] The fiber-reinforced resin composition of the present embodiment (hereinafter also referred to as “composition (I)”) contains:

[0033] Polyolefin resin (A),

[0034] One or more resins (B) selected from the group consisting of polyamide resins (B1) and polyester resins (B2),

[0035] Fiber (C), and

[0036] Modified polyolefin resin (D).

[0037] <Polyolefin resin (A)>

[0038] The polyolefin resin (A) (hereinafter also referred to as "resin (A)") may be a polymer of an olefin such as an α-olefin, a cyclic olefin, a non-conjugated diene, or an aromatic olefin, preferably a polymer containing an α-olefin as a main component. The polymer containing an α-olefin as a main component means that the content of the structural unit derived from the α-olefin in the polymer is preferably 50 mol% or more, more preferably 60 mol% or more, and further preferably 70 mol% or more. The content of the structural unit can be determined, for example, by 13 The determination was carried out by C-NMR method.

[0039] Examples of the α-olefin include α-olefins having 2 to 20 carbon atoms, preferably α-olefins having 2 to 10 carbon atoms, and more preferably α-olefins having 2 to 8 carbon atoms. Specifically, ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 3-methyl-1-butene, and 4-methyl-1-pentene can be mentioned. One or more α-olefins can be used.

[0040] As the polyolefin resin (A), polyethylene such as ethylene homopolymers and copolymers of ethylene and other α-olefins is preferred; polypropylene such as propylene homopolymers and copolymers of propylene and other α-olefins is preferred, polypropylene is more preferred, and propylene homopolymer is particularly preferred. The content of the structural unit derived from ethylene in the polyethylene is preferably 50 mol% or more, more preferably 70 mol% or more, and further preferably 90 mol% or more.

[0041] The polyolefin resin (A) is preferably polypropylene, and the melting point of polypropylene measured by a differential scanning calorimeter (temperature increase rate: 10°C / min) is preferably 130°C or higher, more preferably 140°C or higher, and preferably 180°C or lower, more preferably 170°C or lower.

[0042] The melt flow rate (MFR) of the polyolefin resin (A) (according to JIS K7210, 2.16 kg load) is preferably 0.01 g / 10 min or more, more preferably 0.1 g / 10 min or more, further preferably 1 g / 10 min or more, further preferably 10 g / 10 min or more, particularly preferably 50 g / 10 min or more, and more preferably 300 g / 10 min or less. The measurement temperature of MFR varies depending on the type of polymer. For example, in the case of polypropylene, it is usually 230°C, and in the case of polyethylene, it is usually 190°C. In addition, in order to improve the impregnation into the reinforcing fiber, the melt viscosity η of the polyolefin resin (A) at a shear rate of 120 / sec at 250°C is A It is preferably 30 Pa·s or more, preferably 160 Pa·s or less, and more preferably 100 Pa·s or less.

[0043] The resin (A) may be used alone or in combination of two or more. That is, the resin (A) may be used alone or in combination of two or more of the above-mentioned olefin polymers.

[0044] <Resin (B)>

[0045] The resin (B) is one or more resins selected from the group consisting of polyamide resins (B1) and polyester resins (B2), preferably polyamide resins (B1). The resin (B) is a component that improves the heat resistance, long-term durability, and mechanical properties of the molded body containing the composition (I).

[0046] Melt viscosity η of resin (B) at 250°C at a shear rate of 120 / sec B It is preferably 100 Pa·s or more, and is preferably 200 Pa·s or less, and is more preferably 120 Pa·s or less.

[0047] 《Polyamide resin (B1)》

[0048] Examples of the polyamide resin (B1) include polymers of one or more amino acid monomers selected from compounds having an amino group and a carboxyl group and dehydrated condensates thereof, copolymers of diamines and dicarboxylic acids, and copolymers of the above amino acid monomers, diamines and dicarboxylic acids.

[0049] Examples of the amino acid monomers include amino acids such as aminocaproic acid, aminoundecanoic acid, aminododecanoic acid, and p-aminomethylbenzoic acid; and lactams such as ε-caprolactam, undecanolactam, and ω-lauryllactam. The amino acid monomers may be used alone or in combination.

[0050] Examples of the diamine include ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,11-diaminoundecane, 1,12-diaminododecane, 1,13-diaminotridecane, 1,14-diaminotetradecane, 1,15-diaminopentadecane, 1,16- Aliphatic diamines such as diaminohexadecane, 1,17-diaminoheptadecane, 1,18-diaminooctadecane, 1,19-diaminononadecane, 1,20-diaminoeicosane, 2-methyl-1,5-diaminopentane (2M-5), and 2-methyl-1,8-diaminooctane (2M-8); alicyclic diamines such as cyclohexanediamine and bis(4-aminocyclohexyl)methane; and aromatic diamines such as xylenediamine (p-phenylenediamine, m-phenylenediamine, etc.). One or more diamines may be used.

[0051] Examples of the dicarboxylic acid include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanediic acid, and octadecanedioic acid; alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid; and aromatic dicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid. One or more dicarboxylic acids may be used.

[0052] Specific examples of the polyamide resin (B1) include polyamide 6, polyamide 66, polyamide 610, polyamide 612, polyamide 614, polyamide 11, polyamide 12, polyamide 6T, polyamide 6I, polyamide 9T, polyamide M5T, polyamide 1010, polyamide 1012, polyamide 10T, polyamide MXD6, polyamide 6T / 66, polyamide 6T / 6I, polyamide 6T / 6I / 66, polyamide 6T / 2M-5T, and polyamide 9T / 2M-8T. Among these, polyamide 6 and polyamide 66 are preferred, and polyamide 6 is more preferred.

[0053] The MFR (according to JIS K7210, 2.16 kg load) of the polyamide resin (B1) is preferably 1 g / 10 min or more, more preferably 5 g / 10 min or more, further preferably 10 g / 10 min or more, further preferably 20 g / 10 min or more, and particularly preferably 60 g / 10 min or more. If the MFR value is a certain value or more, when the composition (I) is prepared, there is a tendency that the impregnation of the resin component (i.e., the components including the resin (A), the resin (B) and the resin (D) described later, excluding the fiber (C)) into the fiber (C) described later is excellent. On the other hand, the MFR is preferably 500 g / 10 min or less, more preferably 300 g / 10 min or less, and further preferably 100 g / 10 min or less. The measurement temperature of MFR varies depending on the type of polymer, for example, in the case of polyamide 6, it is usually 230°C, and in the case of polyamide 66, it is usually 270°C.

[0054] The melting point of the polyamide resin (B1) measured by a differential scanning calorimeter (temperature increase rate: 10°C / min) is preferably 200°C or higher, more preferably 210°C or higher, further preferably 220°C or higher, and is preferably 300°C or lower, more preferably 280°C or lower, further preferably 270°C or lower.

[0055] The polyamide resin (B1) can be used alone or in combination of two or more.

[0056] 《Polyester resin (B2)》

[0057] The polyester resin (B2) is a copolymer of one or more selected from polycarboxylic acids and their anhydrides and a polyol, and is a resin having a hydrophilic group in the molecular skeleton including the terminal, and can be produced by a known method. Examples of the hydrophilic group include polyalkylene oxides, sulfonates, carboxyl groups, and neutralized salts thereof.

[0058] Examples of the polyvalent carboxylic acid and its anhydride include aromatic dicarboxylic acids, sulfonate-containing aromatic dicarboxylic acids, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, trifunctional or higher polyvalent carboxylic acids, and anhydrides thereof.

[0059] Examples of the aromatic dicarboxylic acid and anhydride thereof include phthalic acid, terephthalic acid, isophthalic acid, phthalic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, and phthalic anhydride.

[0060] Examples of the sulfonate-containing aromatic dicarboxylic acid include sulfoterephthalate, 5-sulfoisophthalate, and 5-sulfophthalate.

[0061] Examples of the aliphatic dicarboxylic acid and alicyclic dicarboxylic acid and anhydrides thereof include fumaric acid, maleic acid, itaconic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, 1,4-cyclohexanedicarboxylic acid, succinic anhydride, and maleic anhydride.

[0062] Examples of trifunctional or higher polyvalent carboxylic acids and anhydrides thereof include trimellitic acid, pyromellitic acid, trimellitic anhydride, and pyromellitic anhydride.

[0063] Examples of the polyol include diols and trifunctional or higher polyols. Examples of the diol include ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, polybutylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, neopentyl glycol, polybutylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, bisphenol A, and alkylene oxide adducts of bisphenol A. Examples of the trifunctional or higher polyol include trimethylolpropane, glycerol, and pentaerythritol.

[0064] The polyester resin (B2) may be a polymer of one or more monomers selected from compounds having a hydroxyl group and a carboxyl group and dehydrated condensates thereof. Examples of the compound having a hydroxyl group and a carboxyl group include lactic acid.

[0065] Specific examples of the polyester resin (B2) include polybutylene terephthalate, polyethylene terephthalate, polybutylene succinate, polyethylene succinate, and polylactic acid.

[0066] The MFR (according to JIS K7210, 2.16 kg load) of the polyester resin (B2) is preferably 0.1 g / 10 min or more, more preferably 1 g / 10 min or more. On the other hand, the MFR is preferably 100 g / 10 min or less. The measurement temperature of MFR varies depending on the type of polymer, for example, in the case of polybutylene terephthalate, it is usually 230° C., and in the case of polyethylene terephthalate, it is usually 270° C.

[0067] The melting point of the polyester resin (B2) measured by a differential scanning calorimeter (temperature increase rate: 10°C / min) is preferably 200°C or higher, more preferably 210°C or higher, and is preferably 300°C or lower, more preferably 280°C or lower.

[0068] The polyester resin (B2) can be used alone or in combination of two or more.

[0069] <Fiber (C)>

[0070] The composition (I) contains fibers (C) as reinforcing fibers.

[0071] As fiber (C), any fiber of organic fiber and inorganic fiber can be used. For example, glass fiber; carbon fiber; metal fibers such as aluminum fiber, aluminum alloy fiber, copper fiber, brass fiber, steel fiber, stainless steel fiber, titanium fiber; natural fibers such as cotton fiber, silk fiber, wood fiber, cellulose fiber; ceramic fibers such as silicon carbide fiber, silicon nitride fiber, aluminum oxide fiber, zirconium oxide fiber; synthetic fibers formed by synthetic resins such as wholly aromatic polyamide (aramid), wholly aromatic polyester, wholly aromatic polyester amide, wholly aromatic polyether, wholly aromatic polycarbonate, wholly aromatic polyazomethine, polyphenylene sulfide, poly(p-phenylene benzobisoxazole), poly(p-phenylene benzobisthiazole), polybenzimidazole, polyetheretherketone, polyamideimide, polyimide, polytetrafluoroethylene, polyvinyl alcohol, polyolefin, polyarylate, fluorine-based polymer, etc. Among them, glass fiber and carbon fiber are preferred, and glass fiber is more preferred.

[0072] The fiber (C) may be a short fiber or a long fiber. The short fiber may be a short fiber in the form of chopped fibers (cut fibers) or a short fiber in the form of pulp having fibrils. In addition, the fiber (C) may be a single fiber or a fiber formed by twisting a plurality of single fibers.

[0073] The average fiber length of the fiber (C) is preferably 0.01 mm or more, more preferably 0.1 mm or more, further preferably 1 mm or more, preferably 100 mm or less, more preferably 50 mm or less, further preferably 30 mm or less. In this manner, the reinforcing effect of the mechanical properties brought by the reinforcing fibers tends to be fully exhibited, and the dispersibility of the reinforcing fibers in the composition tends to be good, thereby improving the appearance. The ratio of the number of fibers having a fiber length of less than 0.1 mm relative to the total number of reinforcing fibers is preferably 18% or less.

[0074] The average fiber diameter of the fiber (C) is preferably 1 μm or more, more preferably 5 μm or more, preferably 30 μm or less, more preferably 20 μm or less. In this manner, the reinforcing fibers are less likely to be damaged during molding, and the impact strength of the resulting molded product tends to be higher. In addition, the appearance of the molded product becomes better, and there is a tendency to obtain a sufficient reinforcing effect in terms of mechanical properties such as rigidity and heat resistance of the molded product.

[0075] The average fiber length and average fiber diameter can be obtained, for example, by photographing the reinforcing fibers using an optical microscope, measuring the lengths or diameters of 100 reinforcing fibers randomly selected from the obtained photograph, and calculating the arithmetic average of the lengths or diameters.

[0076] Examples of the glass fiber include fibers composed of a glass composition such as A glass, C glass, D glass, E glass, and S glass. In particular, fibers composed of a glass composition of E glass (alkali-free glass) are preferred.

[0077] The glass fiber may be a single fiber or a fiber formed by twisting a plurality of single fibers. The glass fiber may be in any form, for example, a "glass roving" obtained by continuously winding a single fiber or a fiber formed by twisting a plurality of single fibers, a "chopped strand" obtained by cutting to a length of 1 to 10 mm, or a "milled fiber" obtained by pulverizing to a length of about 10 to 500 μm.

[0078] As the carbon fiber, various known carbon fibers can be used, for example, polyacrylonitrile-based, rayon-based, asphalt-based, polyvinyl alcohol-based, regenerated cellulose-based, asphalt-based carbon fibers produced from mesophase asphalt, etc. can be cited. The carbon fiber can be a general-purpose fiber or a high-strength fiber. In addition, the carbon fiber can also be a long fiber, a short fiber, or a regenerated fiber.

[0079] As the natural fiber, cellulose fiber is preferred. The cellulose fiber is preferably cellulose nanofiber, lignocellulose nanofiber, or cellulose microfiber.

[0080] The fiber (C) may be the fiber itself described above (i.e., a fiber that has not been surface treated. Hereinafter referred to as "fiber (C0)"), or may be a fiber formed by surface treating the fiber described above (hereinafter referred to as "surface-treated fiber (C1)"). For example, the "surface-treated fiber (C1)" may be a fiber obtained by surface treatment using various sizing agents (hereinafter referred to as "sizing agent-treated fiber (C1A)"). The aforementioned "sizing agent-treated fiber (C1A)" in most cases comprises the aforementioned fiber (C0) and a sizing agent that coats the fiber (C0). As the aforementioned sizing agent, for example, an acrylic sizing agent, a urethane sizing agent, or an acid copolymer sizing agent can be used. Among them, an acid copolymer sizing agent is preferred.

[0081] Here, when the aforementioned "sizing agent treated fiber (C1A)" is a glass fiber roving obtained by surface treatment with a sizing agent (hereinafter referred to as "sizing agent treated glass fiber roving"), the sizing agent constituting the aforementioned "sizing agent treated glass fiber roving" is preferably an acid copolymer sizing agent from the viewpoint of sufficiently impregnating the sizing agent treated fiber with the resin component. In addition, an acrylic sizing agent is also one of the preferred sizing agents.

[0082] On the other hand, when the aforementioned "sizing agent treated fiber (C1A)" is a fiber other than the aforementioned "sizing agent treated glass fiber roving", for example, a chopped strand obtained by surface treatment with a sizing agent (hereinafter referred to as "sizing agent treated chopped strand"), the sizing agent constituting the "sizing agent treated chopped strand" is not limited to an acid copolymer sizing agent, and may be a sizing agent other than an acid copolymer sizing agent, such as an acrylic sizing agent, a urethane sizing agent, etc. Even such a "sizing agent treated chopped strand" containing a sizing agent other than an acid copolymer sizing agent is preferably impregnated with the resin component in the same manner as the "sizing agent treated chopped strand" containing an acid copolymer sizing agent.

[0083] Furthermore, if necessary, the present invention may contain one or more components selected from the group consisting of a silane coupling agent, a titanate coupling agent, an aluminum coupling agent, a zirconium coupling agent, a borane coupling agent, a curing catalyst, a lubricant, a filler, a thixotropic agent, a tackifier, a wax, a heat stabilizer, a light stabilizer, a fluorescent whitening agent, a foaming agent, a pH adjuster, a leveling agent, a gelation inhibitor, a dispersion stabilizer, an antioxidant, a free radical scavenger, a heat resistance imparting agent, an inorganic filler, an organic filler, a plasticizer, a reinforcing agent, an antibacterial agent, an antifungal agent, an antirust agent, a thermoplastic resin, a thermosetting resin, a pigment, a dye, an electrical conductivity imparting agent, an antistatic agent, a moisture permeability enhancing agent, a hydrophobic agent, an oleophobic agent, a hollow foam, a compound containing crystal water, a flame retardant, a water absorbent, a moisture absorbent, a deodorant, a foam stabilizer, a defoamer, an antifungal agent, a preservative, an antialgae agent, a pigment dispersant, an antiblocking agent, and an antihydrolysis agent.

[0084] Examples of the surface treatment method of the reinforcing fibers using a sizing agent include a method of applying the sizing agent to the surface of the reinforcing fibers using an applicator or the like, a method of immersing the reinforcing fibers in the sizing agent, a method of spraying the sizing agent onto the reinforcing fibers, and a method of contacting the reinforcing fibers with a roll to which the sizing agent is applied. The surface treatment method may be either a batch method or a continuous method.

[0085] In the case of the fiber (C) surface-treated with a sizing agent, the mass ratio of the sizing agent in the fiber (C), i.e., the ignition loss, is preferably 0.1 to 1.5% by mass. The mass ratio of the sizing agent (ignition loss) is measured for the fiber obtained by applying the sizing agent to the reinforcing fiber using, for example, an applicator, and completely volatilizing the volatile substances by drying. When the ignition loss of the sizing agent applied to the surface of the reinforcing fiber is 0.1% by mass or more, the interface between the above-mentioned resin (B) and the fiber (C) can be stabilized, and heat resistance can be exhibited, so it is preferred. On the other hand, when the ignition loss of the sizing agent applied to the surface of the reinforcing fiber is 1.5% by mass or less, it can be confirmed that the physical properties such as heat resistance are improved, so it is preferred.

[0086] The ignition loss of the sizing agent in the fiber (C) is a value measured in accordance with JIS R 3420 (2006) 7.3.2.

[0087] After the surface-treated reinforcing fibers are bundled and wound in a predetermined number, they can be cut and / or crushed as needed to be processed into chopped strands, milled fibers, yarns, rovings, and the like.

[0088] The fibers (C) may be used alone or in combination of two or more.

[0089] <Modified polyolefin resin (D)>

[0090] The modified polyolefin resin (D) is a component that improves the interaction between the polyolefin resin (A) and the resin (B) (for example, acts as a compatibilizer between the resin (A) and the resin (B)) and improves the heat deformation resistance and tensile creep resistance of the molded article containing the composition (I).

[0091] The modified polyolefin resin (D) is a resin obtained by modifying a polyolefin resin (D1) with one or more components (D2) selected from unsaturated carboxylic acids and derivatives thereof, for example.

[0092] As the polyolefin resin (D1), for example, the polyolefin resins described in the item <Polyolefin resin (A)> can be used, and polypropylene is preferred. In addition, other examples of preferred polyolefin resins that can be used as the polyolefin resin (D1) include ethylene-butene copolymers, SEBS, and polyethylene.

[0093] The polyolefin resin (D1) that can be used in the present invention may be used alone or in combination of two or more.

[0094] Examples of the unsaturated carboxylic acid that can be used as the component (D2) include unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, sorbic acid, and angelic acid; and unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, tetrahydrophthalic acid, norbornene dicarboxylic acid, and bicyclo[2.2.1]hept-2-ene-5,6-dicarboxylic acid.

[0095] Examples of the derivative of the unsaturated carboxylic acid that can be used as the component (D2) include anhydrides, halides, esters, amides, imides, and metal salts of unsaturated carboxylic acids. Specific examples include:

[0096] Unsaturated dicarboxylic anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, tetrahydrophthalic anhydride, bicyclo[2.2.1]hept-2-ene-5,6-dicarboxylic anhydride;

[0097] Unsaturated dicarboxylic acid halides such as maleic chloride;

[0098] Acrylic acid esters such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, methacrylic acid esters such as methyl methacrylate and glycidyl methacrylate, maleic acid esters such as monomethyl maleate, monoethyl maleate, dimethyl maleate, diethyl maleate, diethyl maleate, diethyl fumarate, dimethyl itaconate, diethyl citrate, dimethyl tetrahydrophthalate, dimethyl bicyclo[2.2.1]hept-2-ene-5,6-dicarboxylate;

[0099] Acrylamide, maleic acid amide, maleimide, sodium acrylate, sodium methacrylate.

[0100] Among them, unsaturated dicarboxylic acids and their derivatives are preferred, unsaturated dicarboxylic acids and their anhydrides are more preferred, and maleic acid and maleic anhydride are still more preferred. In addition, a combination of acrylic acid ester and glycidyl methacrylate is also one of the preferred examples.

[0101] The component (D2) may be used alone or in combination of two or more.

[0102] As the modification method, a conventionally known method can be used, for example, a method of grafting component (D2) to polyolefin resin (D1) is mentioned. Specifically, component (D2) is grafted to polyolefin resin (D1) to form a graft main chain in the presence of a radical polymerization initiator.

[0103] As the grafting method, a conventionally known method can be used, for example, a solution method and a melt kneading method can be mentioned. For example, the following methods can be mentioned: a method in which the polyolefin resin (D1) is suspended or dissolved in a solvent, and the mixed component (D2) and a radical polymerization initiator are added at a temperature of usually 80 to 200°C to carry out graft polymerization; a method in which the component (D2) and a radical polymerization initiator are brought into contact under melt kneading at a temperature above the melting point of the polyolefin resin (D1), for example, 180 to 300°C.

[0104] As the above-mentioned solvent used in the solution method, for example, there can be mentioned aromatic hydrocarbon solvents such as toluene and xylene; aliphatic hydrocarbon solvents such as hexane, heptane, octane, and decane; alicyclic hydrocarbon solvents such as cyclohexane and methylcyclohexane; chlorinated hydrocarbon solvents such as trichloroethylene, perchloroethylene, dichloroethylene, dichloroethane, and chlorobenzene; aliphatic alcohol solvents such as ethanol and isopropanol; ketone solvents such as acetone, methyl isobutyl ketone, and methyl ethyl ketone; ester solvents such as methyl acetate, ethyl acetate, and butyl acetate. One or more solvents can be used.

[0105] Examples of the radical polymerization initiator include organic peroxides and azo compounds. Examples of the organic peroxide include benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, m-toluoyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, (2,5-dimethyl-2,5-bis(tert-butylperoxide)hexane, 2,5-dimethyl-2,5-bis(tert-butylperoxide)-3-hexyne, lauroyl peroxide, tert-butyl peroxyacetate, 2,5-dimethyl-2,5-di(benzoylperoxide)hexane, tert-butyl peroxybenzoate, tert-butyl peroxyisobutyrate, tert-butyl peroxyphenylacetate, tert-butyl peroxy-s-octanoate, tert-butyl peroxypivalate, cumyl peroxypivalate, and tert-butyl peroxyethylacetate. Examples of the azo compound include azoisobutyronitrile and dimethyl azoisobutyrate. One or more radical polymerization initiators may be used.

[0106] The modified polyolefin resin (D) can also be obtained by copolymerizing an olefin with the component (D2). As the olefin, the olefin used to form the polyolefin resin (D1) can be used. As the copolymerization method, for example, a conventionally known free radical copolymerization method can be used.

[0107] The content of the structure derived from component (D2) in the modified polyolefin resin (D) is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and preferably 5% by mass or less, more preferably 1% by mass or less. For the above content, for example, in the case of a maleic acid-modified polyolefin resin, the infrared absorption spectrum of the resin can be measured based on 1670 to 1810 cm -1The peak area of ​​​​the compound is determined by a separately prepared calibration curve. When using a component (D2) other than maleic acid, the above content can also be determined by infrared absorption spectroscopy or the like.

[0108] The modified polyolefin resin (D) is preferably one or more resins selected from modified polypropylene and modified polyethylene, more preferably one or more resins selected from maleic acid-modified polypropylene, maleic anhydride-modified polypropylene, maleic acid-modified polyethylene and maleic anhydride-modified polyethylene, and further preferably one or more resins selected from maleic acid-modified polypropylene and maleic anhydride-modified polypropylene.

[0109] The modified polyolefin resin (D) may be used alone or in combination of two or more.

[0110] <Other ingredients>

[0111] The composition (I) may contain other ingredients other than the above within the scope that does not hinder the purpose of the present invention. As other ingredients, for example, other thermoplastic resins other than polyolefin resin (A), resin (B) and modified polyolefin resin (D), flame retardants, flame retardant additives, fillers, colorants, antibacterial agents, antistatic agents can be cited. These can be used alone or in combination.

[0112] Examples of other thermoplastic resins include styrene-based thermoplastic elastomers such as styrene-butadiene-styrene copolymers (SBS), styrene-isoprene-styrene copolymers (SIS), styrene-ethylene / butylene-styrene copolymers (SEBS), and styrene-ethylene / propylene-styrene copolymers (SEPS).

[0113] As flame retardants, for example, halogen flame retardants (for example, halogenated aromatic compounds), phosphorus flame retardants (for example, nitrogen-containing phosphate compounds, phosphate esters), nitrogen flame retardants (for example, guanidine, triazine, melamine and their derivatives), inorganic flame retardants (for example, metal hydroxides), boron flame retardants, silicone flame retardants, sulfur flame retardants, and red phosphorus flame retardants can be cited.

[0114] Examples of the flame retardant aid include various antimony compounds, metal compounds containing zinc, metal compounds containing bismuth, magnesium hydroxide, and clay silicates.

[0115] As fillers, for example, glass components (e.g., glass beads, glass flakes), silica, graphite, silicic acid compounds (e.g., calcium silicate, aluminum silicate, kaolin, talc, clay), metal oxides (e.g., iron oxide, titanium oxide, zinc oxide, antimony oxide, aluminum oxide), carbonates and sulfates of metals such as calcium, magnesium, and zinc.

[0116] Examples of the colorant include pigments and dyes.

[0117] <Content of each ingredient>

[0118] By using the composition (I), a molded product can be produced which has excellent tensile creep resistance, flexural modulus and flexural strength while maintaining high heat deformation resistance under high load.

[0119] Preferred contents of the components in composition (I) are as follows.

[0120] In 100 parts by mass of the total content of the resin (A), the resin (B) and the fiber (C), the content of the resin (A) is 5 parts by mass or more, preferably 10 parts by mass or more, more preferably 15 parts by mass or more; and is 60 parts by mass or less, preferably 50 parts by mass or less, more preferably 40 parts by mass or less, further preferably 33 parts by mass or less, and particularly preferably 27 parts by mass or less. If the content of the resin (A) is 5 to 60 parts by mass, it is excellent in terms of cost and specific gravity.

[0121] In the total of 100 parts by mass of the content of the resin (A), the resin (B) and the fiber (C), the content of the resin (B) is 5 parts by mass or more, preferably 10 parts by mass or more; and is 60 parts by mass or less, preferably 50 parts by mass or less. When the content of the resin (B) is 5 to 60 parts by mass, the obtained molded body has excellent heat resistance and tensile creep resistance.

[0122] In the total of 100 parts by mass of the content of the resin (A), the resin (B) and the fiber (C), the content of the fiber (C) is 10 parts by mass or more, preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and further preferably 35 parts by mass or more; and is 70 parts by mass or less, preferably 60 parts by mass or less. When the content of the fiber (C) is 10 to 70 parts by mass, the obtained molded body has excellent flexural modulus and flexural strength.

[0123] The content of the modified polyolefin resin (D) is 0.05 parts by mass or more, preferably 0.1 parts by mass or more, and 0.95 parts by mass or less, preferably 0.7 parts by mass or less, and more preferably 0.5 parts by mass or less, relative to 100 parts by mass of the total content of the resin (A), the resin (B) and the fiber (C). When the content of the modified polyolefin resin (D) is above the aforementioned lower limit and below the aforementioned upper limit, for example, when it is 0.05 to 0.95 parts by mass, the high heat deformation resistance under high load of the molded body can be maintained, and the tensile creep resistance of the molded body is improved compared to the case where the content is outside this range.

[0124] In 100 parts by mass of the total content of the resin (A) and the resin (B), the content of the resin (B) is preferably 8 parts by mass or more, more preferably 20 parts by mass or more, further preferably 33 parts by mass or more, further preferably 45 parts by mass or more, and particularly preferably 55 parts by mass or more; preferably 92 parts by mass or less, more preferably 80 parts by mass or less, and further preferably 75 parts by mass or less. If the content of the resin (B) relative to the total of the resin (A) and the resin (B) is above the aforementioned lower limit and below the aforementioned upper limit, for example 8 to 92 parts by mass, the obtained molded body has excellent heat resistance and tensile creep resistance.

[0125] The total content of the resin (A), the resin (B), the fiber (C) and the modified polyolefin resin (D) in 100% by mass of the entire composition (I) is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more.

[0126] <Ratio and Range of Melt Viscosity>

[0127] In the composition (I), the melt viscosity η of the resin (A) at 250°C at a shear rate of 120 / sec is A Melt viscosity η of resin (B) at 250°C at a shear rate of 120 / sec B The ratio η A / η B In the range of 0.3 to 1.3, the viscosity of the composition obtained by melt-kneading only the resin component of the composition (I) excluding the fiber (C) is preferably in the range of 40 to 130 Pa·s. Within the above range, the impregnation of the resin into the reinforcing fiber is excellent, that is, the proportion of the resin present in the peripheral part of the reinforcing fiber is large. As a result, the mechanical properties of the composition (I) are excellent.

[0128] <Method for producing fiber-reinforced resin composition>

[0129] The composition (I) can be produced by melt-kneading the above-mentioned components. The melt-kneading temperature is a temperature higher than the melting temperature of the resin containing the components (for example, resin (A), resin (B), resin (D)), for example, 5 to 100°C, and preferably a temperature higher than the melting point of the resin having the highest melting point among the resin containing the components by 10 to 60°C. In addition, the melt-kneading treatment time is, for example, 30 seconds to 15 minutes, preferably 1 to 10 minutes.

[0130] The composition (I) may be short fiber reinforced resin pellets or long fiber reinforced resin pellets.

[0131] When the composition (I) is a short fiber reinforced resin pellet, the above-mentioned components can be fully melt-mixed and dispersed in an extruder, etc. with a roller mill, a Banbury mixer, a kneader, etc. to produce. The above-mentioned components can also be dry-mixed using a drum mixer, a Henschel mixer, a ribbon mixer, etc., and melt-mixed using a single screw extruder, a twin screw extruder, etc. to produce a pellet-shaped molding material. In this method, the fiber (C) can be put in from any place on the top or side of the extruder. In addition, in this method, it is also possible to melt-mix with the fiber (C) after all or part of the components other than the fiber (C) are melt-mixed separately.

[0132] When the composition (I) is a long fiber reinforced resin pellet, it can be produced by a known method such as a drawing method. It is also possible to melt-knead a portion of the above components separately, and then add the remaining components and melt-knead them. For example, a glass fiber roving can be introduced into an impregnation mold, and after the molten resin is uniformly impregnated between the filaments, it can be cut into a desired length, thereby granulating.

[0133] [Molding body]

[0134] The composition (I) can be processed into a molded body by conventional molding methods such as injection molding, extrusion molding, and compression molding. In the case of injection molding, for example, the above-mentioned short fiber reinforced resin pellets or long fiber reinforced resin pellets can be used for injection molding. In this case, when the short fiber reinforced resin pellets or long fiber reinforced resin pellets are fed from the feed hopper of the injection molding machine, other resins, such as the polyolefin resins recorded in the item <Polyolefin Resin (A)>, can also be further added. In addition, the short fiber reinforced resin pellets or long fiber reinforced resin pellets can also be fed from the exhaust port of the injection molding machine, and other resins, such as the polyolefin resins recorded in the item <Polyolefin Resin (A)>, can be fed from the feed hopper, mixed in the injection molding machine, and molded.

[0135] Alternatively, the polyolefin resin (A), the resin (B), the fiber (C) and the modified polyolefin resin (D) may be melt-kneaded and molded in an injection molding machine without passing through the short fiber reinforced resin pellets and the long fiber reinforced resin pellets. In this case, the fiber (C) may be fed from the hopper of the injection molding machine or from the side such as the exhaust port.

[0136] The molded article of the present embodiment contains the composition (I). For example, the molded article of the present embodiment may be entirely formed of the composition (I) or may contain a part formed of the composition (I).

[0137] The molded article can be used in a wide range of applications, from household products such as daily necessities and leisure products to general industrial applications and industrial products. For example, the molded article can be used in home appliance material parts, communication equipment parts, electrical parts, electronic parts, automobile parts, parts of vehicles other than automobiles, ships, aircraft materials, mechanical parts, building material-related parts, civil engineering parts, agricultural materials, electric tool parts, food containers, films, sheets, and fibers.

[0138] As automobile parts, it can be applied to various parts such as power transmission parts (because the heat resistance can be improved), mechanical parts (because the tensile creep resistance can be improved), and outer panel parts (because the bending characteristics can be improved), and can also be applied to other parts. When specifically mentioned, the parts include intake manifold, oil pan, cylinder head, cylinder head cover, engine hood, hood, mirror bracket, interior console, sliding roof, sliding roof frame, front door, rear door, sliding door, front module, door module, fender, wheel cover, fuel tank, belt, ceiling cover, convertible top, armrest, door trim, rear storage box, sun visor, wheel cover, mattress cover, airbag, insulation material, wire coating material, electrical insulation material, surface covering material, floor material, skirting board, pallet, cover body, plywood, ceiling, partition, side wall, wallpaper, wall material, exterior decoration material, interior decoration material, roof material, sound insulation board, heat insulation board.

[0139] As home appliance material parts, communication equipment parts, electrical parts, and electronic parts, for example, there can be mentioned battery pack parts (outer covers, trays, module housings), printers, personal computers, word processors, keyboards, small information terminals (PDAs), stereo headphones, mobile phones, telephones, fax machines, copiers, electronic cash registers (ECRs), calculators, electronic notepads, electronic dictionaries, cards, stands, stationery and other office OA equipment; washing machines, refrigerators, vacuum cleaners, microwave ovens, lighting fixtures, game consoles, irons, heaters and other home appliances; TVs, VTRs, video cameras, radios, recorders, mini discs, CD players, speakers, liquid crystal displays and other AV equipment; connectors, relays, capacitors, switches, printed circuit boards, coil frames, semiconductor sealing materials, wires, cables, transformers, deflection coils, switchboards, and clocks.

[0140] Examples of daily necessities include plywood, synthetic fiber boards, buckets, containers, bags, housings, goggles, skis, rackets, tents, bicycles, musical instruments, and other daily necessities and sports goods.

[0141] Example

[0142] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited to the following Examples. In the following description, "parts" means "parts by mass".

[0143] The raw materials and physical properties used in Examples and Comparative Examples are shown below.

[0144] Polyolefin resin (A)

[0145] PP1: Polypropylene

[0146] J13B manufactured by Prime Polymer Co., Ltd., MFR (according to JIS K7210, 230°C, 2.16 kg load): 220 g / 10 min, melt viscosity η A (250℃, 120 / sec): 35.8Pa·s

[0147] PP2: Polypropylene

[0148] S119 manufactured by Prime Polymer Co., Ltd., MFR (according to JIS K7210, 230°C, 2.16 kg load): 60 g / 10 min, melt viscosity η A (250℃, 120 / sec): 89.4Pa·s

[0149] PP3: Polypropylene

[0150] J137G manufactured by Prime Polymer Co., Ltd., MFR (according to JIS K7210, 230°C, 2.16 kg load): 30 g / 10 min, melt viscosity η A (250℃, 120 / sec): 152Pa·s

[0151] Polyamide resin (B1)

[0152] PA6-1: Polyamide 6

[0153] Toray CM1007, MFR (according to JIS K7210, 230°C, 2.16 kg load): 67 g / 10 min, melt viscosity η B (250℃, 120 / sec): 112Pa·s

[0154] PA6-2: Polyamide 6

[0155] 1013B manufactured by Ube Industries, MFR (according to JIS K7210, 230°C, 2.16 kg load): 30 g / 10 min, melt viscosity η B (250℃, 120 / sec): 192Pa·s

[0156] Polyester resin (B2)

[0157] ·PBT: Polybutylene terephthalate

[0158] Polyplastics 300FP, MFR (according to JIS K7210, 230°C, 2.16 kg load): 3 g / 10 min, melt viscosity η B (250℃, 120 / sec): 115Pa·s

[0159] Fiber (C)

[0160] GF1: Glass fiber chopped strands surface treated with an acrylic sizing agent (length 3 mm, filament diameter 11 μm)

[0161] GF2: Glass fiber chopped strands (length 4 mm, filament diameter 13 μm) surface treated with an acid-modified polypropylene sizing agent

[0162] GF3: Glass fiber chopped strands surface treated with a urethane sizing agent (length 3 mm, filament diameter 11 μm)

[0163] CF: Carbon fiber chopped strands surface-treated with a urethane sizing agent (length 4 mm, filament diameter 7 μm)

[0164] ·LGF1: Glass fiber roving surface treated with an acrylic sizing agent (filament diameter 17 μm, TEX number 2400 g / 1000 m)

[0165] ·LGF2: Glass fiber roving surface treated with an acid copolymer sizing agent (filament diameter 17 μm, TEX number 2400 g / 1000 m)

[0166] Modified polyolefin resin (D)

[0167] Modified PP: Maleic acid modified polypropylene

[0168] Mitsui Chemicals, Inc., ADMER, product number "AT2606", content of structure derived from maleic acid: 0.6 mass%

[0169] Modified EBR: Maleic acid modified α-olefin copolymer (maleic acid modified ethylene-butene copolymer)

[0170] Mitsui Chemicals, Inc., TAFMER, product number "MH7020", content of structure derived from maleic acid: 0.7 mass%

[0171] Modified SEBS: Maleic acid modified hydrogenated styrene thermoplastic elastomer

[0172] Made by Asahi Kasei Corporation, Tuftec product number "M1943"

[0173] Modified PE: Acrylate-Glycidyl Methacrylate Modified Polyethylene

[0174] Lotader, product number "AX8900", content of structure derived from maleic acid: 24 mass%

[0175] [Example 1]

[0176] 50 parts of PP1 as a polyolefin resin (A), 10 parts of PA6-1 as a polyamide resin (B1), and 0.1 parts of modified PP as a modified polyolefin resin (D) were pre-mixed by dry blending and supplied to the feed hopper of a twin-screw melt-kneading extruder ("KZW15TW-30MG-NH" manufactured by Technovel, screw diameter 15 mm, L / D = 30). On the other hand, 40 parts of GF1 as a fiber (C) were supplied to the twin-screw melt-kneading extruder. The fiber-reinforced resin composition was prepared by heating and melt-kneading at a temperature of 250°C.

[0177] The fiber-reinforced resin composition obtained in the above manner was injection molded using an injection molding machine (manufactured by Toshiba Machine Co., Ltd., "EC75XIII") under injection conditions of a set temperature of 250°C and a mold temperature of 60°C to produce a strip test piece for evaluation test (length 80 mm×width 10 mm×thickness 4 mm) and a dumbbell-shaped test piece for evaluation test (in accordance with JIS K7139 (ISO 3176:93)) formed of the above fiber-reinforced resin composition.

[0178] [Examples 2 to 19, Comparative Examples 1 to 8]

[0179] The fiber-reinforced resin compositions and test pieces were prepared under the same conditions as in Example 1 except that the compounding compositions were changed as described in Tables 1 to 5. The numerical values ​​shown for each component in Tables 1 to 5 are compounding amounts based on parts by mass. It should be noted that in Examples 16 to 19 and Comparative Example 8, a polyester resin (B2) was compounded instead of the polyamide resin (B1).

[0180] The following evaluation tests were performed using these test pieces. The results are shown in Tables 1 to 5.

[0181] [Example 20]

[0182] PP1 as polyolefin (A), PA6-1 as polyamide resin (B1), and modified PP as modified polyolefin resin (D) were blended in the mass parts shown in Table 6 and fed into the feed hopper of a twin-screw melt-kneading extruder whose temperature was adjusted to 295° C. In addition, the glass fiber roving (LGF2) shown in Table 1 as fiber (C) was expanded and opened at a rate of the mass parts shown in Table 6, and the resin component (i.e., a mixture of polyolefin (A), polyamide resin (B1) and modified polyolefin resin (D)) from the extruder and the above-mentioned glass fiber were supplied to the impregnation die, impregnated, cooled and solidified, and then cut into pellets of 9 mm in length using a strand cutter. The obtained pelletized fiber-reinforced resin composition was injection molded in the same manner as in Example 1 to produce a strip test piece for evaluation test (length 80 mm×width 10 mm×thickness 4 mm) and a dumbbell-shaped test piece for evaluation test (in accordance with JIS K7139 (ISO 3176:93)) formed of the fiber-reinforced resin composition.

[0183] The following evaluation tests were performed using these test pieces. The results are shown in Table 6.

[0184] [Examples 21 to 24 and Comparative Examples 9 to 10]

[0185] Fiber-reinforced resin compositions and test pieces were prepared under the same conditions as in Example 20 except that the compounding composition was changed as described in Table 6. In Table 6, the numerical value shown for each component is the compounding amount based on parts by mass.

[0186] The following evaluation tests were performed on each of these test pieces. The results are shown in Table 6.

[0187] <Evaluation of Heat Deformation Temperature>

[0188] The heat deformation temperature was measured using the long test piece for evaluation test in accordance with ISO 751-1 (1.8 MPa load) using an "Automatic HDT Tester" manufactured by Toyo Seiki Seisaku-sho, Ltd.

[0189] <Evaluation of bending test>

[0190] A bending test was carried out using the evaluation test strip test piece in accordance with ISO 178 to determine the bending modulus FM (MPa) and the bending strength FS (MPa) in the stress-strain curve.

[0191] <Evaluation of Tensile Creep Strain>

[0192] The tensile creep strain was measured using the dumbbell-shaped test piece for the evaluation test of JIS K7139 as the test piece under the conditions of an initial stress of 5.0 MPa, a test temperature of 80°C and 120°C, and a test time of 100 hours. However, for Examples 14 to 24 and Comparative Examples 5 to 10, the initial stress was changed to 20 MPa, and the test temperature was set to 80°C, and the same test was performed.

[0193] In addition, the impregnation property with respect to the glass fiber was evaluated as follows using the resin components other than the fiber (C) used in each example and comparative example. This evaluation was used as the evaluation of the impregnation property in the fiber-reinforced resin composition obtained in each example and comparative example. The melt viscosity was also evaluated by the following method.

[0194] <Evaluation of impregnation properties>

[0195] Regarding the evaluation of impregnation, use Figure 1 In the mold shown, glass fiber roving (fiber diameter: 17 μm, TEX number 2400 g / 1000 m) is placed in the installation spaces 1 and 2 of 14 mm width, 250 mm length and 4 mm depth, and is fixed to a frame with a spring by a clamp.

[0196] Using the twin-screw melt-kneading extruder described in Example 1, only the resin components described in each example and comparative example except the fiber (C) were melt-kneaded, and the kneaded sample was press-molded at 270°C to produce a pressurized sheet with a thickness of 100 μm. The produced pressurized sheet (thickness of 100 μm) was cut into two strips with a size of 14 mm in width and 200 mm in length, and the strip-shaped pressurized sheets were respectively set on the glass fiber rovings set in the above-mentioned setting spaces 1 and 2. A mold cover was placed on it, and a manual press ("MP-WCH" manufactured by Toyo Seiki Co., Ltd.) was used to pressurize to produce a sample. As the pressurization conditions, the pressurization temperature was 280°C, the pressurization was applied to 5 MPa, and after preheating for 10 minutes, pressurization was performed under the condition of 10 MPa and heating for 2 minutes. Only the central part of the obtained glass fiber roving impregnated with resin was cut out, and calcined in an electric furnace ("FO300" manufactured by Yamato Co., Ltd.) at 500°C for 1 hour, and the mass of the remaining glass fiber was measured. Based on the mass of the glass fiber before and after calcination, the glass fiber ratio (mass %) in the sample was calculated using the following formula.

[0197] Glass fiber ratio (%) = {mass of only glass fiber after firing} ÷ {mass of glass fiber including impregnated resin before firing} × 100

[0198] The impregnation of the kneaded product containing only the resin component without containing the fiber into the glass fiber was evaluated based on the glass fiber ratio in the sample. Here, the impregnation was evaluated based on the following criteria.

[0199] ·Impermeability evaluation criteria

[0200] ○: The glass fiber mass ratio (mass %) in the sample is less than 80 mass %

[0201] ×: The glass fiber mass ratio (mass %) in the sample is 80 mass % or more

[0202] The resin kneaded material with poor impregnation has poor permeability into the glass fiber, so even if pressurized, it remains unimpregnated with the resin into the glass fiber and melts and diffuses in the mold. Therefore, the mass ratio of glass fiber in the fired sample becomes high.

[0203] <Evaluation of raising>

[0204] 100 pellets obtained in Examples 20 to 24 and Comparative Examples 9 to 10 were randomly collected and evaluated for fuzzing. The pellets were subjected to a grinding test for a specified time (5 seconds), crushed, and the generation of fuzz was observed. If there is a portion of the glass fiber roving in the pellets to which the resin is not attached, fuzz will occur after the grinding test, and the pellets will bulge after crushing. The case of bulging is recorded as ×, the case of slight bulging is recorded as △, and the case of almost no bulging is recorded as 0.

[0205] <Evaluation of Melt Viscosity>

[0206] Melt viscosity ratio η A / η B

[0207] The melt viscosity η of each polyolefin resin (A) and resin (B) at a shear rate of 120 / sec at 250°C was measured in accordance with JIS K7199:1999 (ISO 11443:1995). A and η B , calculate η A With η B Ratio.

[0208] Melt viscosity of resin pellets of a composition obtained by melt-kneading only the resin components of the composition (I) excluding the fibers (C)

[0209] Using resin pellets of a composition obtained by melt-kneading only the resin components of composition (I) other than the fibers (C) used in the evaluation of impregnation properties, the melt viscosity at a shear rate of 120 / sec at 250°C was measured in accordance with JIS K7199:1999 (ISO 11443:1995).

[0210] [Table 1]

[0211]

[0212] [Table 2] [Table 2

[0213]

[0214] [Table 3] [Table 3

[0215]

[0216] [Table 4]

[0217]

[0218] [Table 5]

[0219]

[0220] [Table 6]

[0221]

Claims

1. A fiber-reinforced resin composition comprising: Polyolefin resin (A), One or more resins (B) selected from the group consisting of polyamide resins (B1) and polyester resins (B2), Fiber (C), and Modified polyolefin resin (D); In 100 parts by weight of the total content of the polyolefin resin (A), the resin (B) and the fiber (C), the content of the polyolefin resin (A) is 5 to 60 parts by weight, the content of the resin (B) is 5 to 60 parts by weight, and the content of the fiber (C) is 10 to 70 parts by weight, The content of the modified polyolefin resin (D) is 0.05 to 0.95 parts by mass relative to 100 parts by mass of the total content of the polyolefin resin (A), the resin (B) and the fiber (C). The melt viscosity η of the polyolefin resin (A) at 250°C at a shear rate of 120 / sec A 30Pa·s or more and 100Pa·s or less, The melt viscosity η of the resin (B) at 250°C at a shear rate of 120 / sec B 100Pa·s or more and 120Pa·s or less, The melt viscosity η A The melt viscosity η B The ratio η A / η B In the range of 0.3 to 1.3, The polyolefin resin (A) is a polymer containing 50 mol % or more of a structural unit derived from an α-olefin, The fiber (C) is at least one selected from glass fiber and carbon fiber.

2. The fiber-reinforced resin composition according to claim 1, wherein The resin (B) is the polyamide resin (B1).

3. The fiber-reinforced resin composition according to claim 1, wherein The polyamide resin (B1) is polyamide 6.

4. The fiber-reinforced resin composition according to claim 1, wherein The content of the resin (B) is 8 to 92 parts by mass in 100 parts by mass of the total content of the polyolefin resin (A) and the resin (B).

5. The fiber-reinforced resin composition according to any one of claims 1 to 4, wherein The polyolefin resin (A) is polypropylene.

6. The fiber-reinforced resin composition according to claim 1, wherein The polyamide resin (B1) is polyamide 6, and the polyester resin (B2) is polybutylene terephthalate. 7 . A molded article comprising the fiber-reinforced resin composition according to claim 1 . The molded article according to claim 7 , which is an automobile part.

Citation Information

Patent Citations

  • Heat-resistant fiber-reinforced resin composition

    JP2003231758A

  • Glass fiber reinforced thermoplastic resin composition and forming products

    CN101389711A

  • Resin composition, resin molded article, and method of preparing resin composition

    CN106554563A